DIGITAL LITERACY IN ENGLISH LEARNING FOR GENERATION ALPHA: A CASE STUDY AT SMP ISLAM AL AZHAAR TULUNGAGUNG - Nisa, Fauziatun; Ris'ah, Umniyati; Shofiya, Arina; Nurhayati, Dwi Astuti Wahyu (STKIP Persada Khatulistiwa Sintang, 2025)
This article discusses the results of qualitative research on the application of digital literacy in English language learning for Generation Alpha students at SMP Islam Al-Azhaar Tulungagung. The research aims to explore the technology-based learning methods implemented at the school, as well as its impact on the teaching-learning process. As information technology advances, digital literacy has become an essential skill for students to access, evaluate and utilize information effectively. Some of the innovative approaches identified in this study include the use of digital libraries, learning apps and interactive platforms to enhance the learning experience. The results show that the integration of digital literacy in learning not only creates a more enjoyable and varied learning atmosphere but also increases students' engagement in the learning process. In addition, digital literacy is able to prepare students to face global challenges in the future. However, this study also found some significant challenges, such as limited access to technology, lack of teacher training, and different levels of understanding of technology between students and educators. Despite the obstacles, the implementation of digital literacy has great potential in improving the quality of learning at Al-Azhaar Tulungagung Islamic Junior High School, especially in creating a more competent generation in the digital era.Keywords: Digital literacy, Generation Alpha